Identifikasi Potensi Ekonomi Maritim Provinsi Banten: Model Ekonomi Biru Menggunakan AHP Analysis - Maulani, Syifa Fajar; Nurmalia, Lulu; Tsani, Rubby Rahman; Wati, Rohmah; Ma’ruf, Ma’ruf; Mauluddin, Fikri Muhammad; Ardiansyah, Wibi; Susilawati, Susilawati; Wardana, Deni (Eqien - Jurnal Ekonomi dan Bisnis, 2024)
This study aims to analyze the maritime economic sectors in Banten Province, Indonesia, using the Analytic Hierarchy Process (AHP) and Location Quotient (LQ) methods. The results show that maritime transportation is the dominant sector, followed by marine tourism and fisheries. The study suggests that strategic implementation is vital for sustainable development, emphasizing environmental impact and government support for foundational sectors, especially maritime transportation. The Blue Economy concept guides aligned economic growth, environmental preservation, and societal well-being. This study provides insights for optimizing maritime economic potential and realizing a sustainable Blue Economy model in Banten Province.